GEOPOLÍTICA DE LA CRISIS EN LA GESTIÓN DE LOS DESECHOS SÓLIDOS DOMÉSTICOS (GRAN ÁREA METROPOLITANA DE COSTA RICA: 1950-2005) - Ramírez Boza, Mario (2005)
The following is a study of the economic and political power relationships (both legal and illegitimate ones) during the 1950-2005 period which have led to the currentcrisis in domestic solid waste management in Costa Rica. Additionally, its territorial coverage is taken into consideration (as policies have been drawn taking into accountGreat Metropolitan Area specificities but have been mechanically applied at the national level), as well as the various interests held by private groups and individualswho have benefited from them, the rights of citizens who have been affected (in spite of the management possibilities community organizations and the third sector have),and the harm brought upon credibility of State agencies and institutions.